The role and the management of research at the university with reference to the Universiti Pertanian Malaysia. - Abdul Rahman, Omar (1976)
The role and the management of research as it applies to the University is discussed. Where applicable mention is made of the situation as it affects the Universiti Pertanian Malaysia (U.P.M.). It is concluded that research is an integral part of modern University, especially a service-orientated one like the Universiti Pertanian Malaysia where it forms the basis for both teaching and extension. In general terms it is emphasised that research at a service-orientated University should be problem-centred and multidisciplinary in approach. It is the researcher who is of paramount importance in research. Any other factors are supportive. Research management should, therefore, be directed towards increasing the efficiency and productivity of the researcher, and the maintenance of an environment optimal for the need of the researcher and not of bureaucracy. The needs of research should not, however, be provided for at the expense of the teaching responsibility.